Identifikasi Drug Related Problems (DRPs) Pada Pasien Diabetes Melitus Tipe 2 Di Rawat Inap - Putri M. Soleh, Ayu Angger; Indriani Putri, Lolita (Fakultas Ilmu Kesehatan Universitas Gresik, 2022)
Diabetes mellitus (DM) is a group of metabolic disorders that cause chronically elevated blood sugar levels. Patients with Type-2 Diabetes (DM-2), with complications or comorbidities, often receive polypharmacy. Polypharmacy has the potential to cause drug related problems (DRPs). The purpose of this study was to determine the pattern of prescribing antidiabetic drugs and DRPs in DM-2 patients at the Mitra Sehat Medika Hospital, Pasuruan, from March 1, 2021 to August 30, 2021. The study design was observational with retrospective data collection. The research data was obtained from the patient's medical records, then the data were analyzed descriptively and the DRPs were identified using the Pharmaceutical Care Network Europe (PCNE) version 9.00. The results obtained 78 patients, 33 men (42.3%) and 45 women (45.7%). The majority of the age group experiencing DM-2 were 45–59 years old (n = 62; 79.5%). Hypertension was the most common comorbid (n = 12; 25.0%). The average length of hospitalization was 3.76 ± 1.009 days. After being hospitalized, 75 patients had controlled sugar level (96.2%), other patients referred to another hospitals. All patients (n = 78; 100.0%) received polypharmacy therapy (≥ 5 drugs). The pattern of prescribing antidiabetic drugs used was a combination of insulin glulisine + insulin glargine (n = 54; 69.2%), insulin glulisine (n = 19; 24.4%), the combination of insulin glulisine + insulin glargine + glimepiride (n = 4; 5.1%), the combination of insulin glulisine + glimepiride (n = 1; 1.3%). The occurrence of DRPs was related to the effectiveness of the treatment (n = 23; 29.5%), and the safety of the treatment (n = 15; 19.2%).